I think I understand your question. You are comparing the y-intercept value from each of the equations... Right?

I believe that the easiest way to compare y-intercept values is to put each of the equations in the slope-intercept form --> y = mx + b (b is the y-intercept)

So...

3x + y = -3

will become...

Y = -3x + (-3) by subtracting the 3x from both sides

And...

4y - 12 = 5x

will become...

4y = 5x + 12 by adding 12 to each side and...

Y = (5/4)x + 3 by dividing every term by 4 since y needs to be on the left all by itself.

By looking at the end equations you can see that the y-intercepts are -3 and 3. I'm not sure what comparison you're asked to make, but I hope this much helps :)

I believe that the easiest way to compare y-intercept values is to put each of the equations in the slope-intercept form --> y = mx + b (b is the y-intercept)

So...

3x + y = -3

will become...

Y = -3x + (-3) by subtracting the 3x from both sides

And...

4y - 12 = 5x

will become...

4y = 5x + 12 by adding 12 to each side and...

Y = (5/4)x + 3 by dividing every term by 4 since y needs to be on the left all by itself.

By looking at the end equations you can see that the y-intercepts are -3 and 3. I'm not sure what comparison you're asked to make, but I hope this much helps :)